Gastric-type mucinous endocervical adenocarcinomas: A case report and literature review - Lu, Junling; Na, Jing; Li, Ya; Wang, Xinyou; Wang, Jun; Han, Shichao (Frontiers in Cellular and Infection Microbiology, 2022)
Gastric type mucinous endocervical adenocarcinomas (GAS) are new variant types of cervical adenocarcinomas according to 2014 WHO classification. GAS is a unique disease that can be differentiated from typical adenocarcinomas, it is less common and more aggressive, likely to have deep invasion and horizontal diffusion, invade the uterine and vagina, and early distant metastases, and a lower 5-year survival rate compared to usual type cervical cancer. At present, initial treatment and postoperative adjuvant therapy are not conclusive, but early detection and early treatment is a consensus that can improve prognosis. Most of its occurrence has nothing to do with HPV infection. Whether it is only negative for the subtypes that can be detected at present, and whether it may be an unknown subtype of infection needs to be further explored in the future. The clinical symptoms commonly include aqueous secretion, lower abdominal pain and Elevated Serum CA199 levels, which may be helpful for diagnosis. MRI and PET-CT can help to describe the characteristics of lesions and judge the state of the systemic metastasis. We believe that early detection and surgical treatment will give patients more benefits. Looking for potential gene and molecular changes and establishing biomarkers to identify molecular targets will be the key to early identification and target therapy.